2005
DOI: 10.1083/jcb.200509124
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the nucleus and cytoplasm: Role of the LINC complex

Abstract: The nuclear envelope defines the barrier between the nucleus and cytoplasm and features inner and outer membranes separated by a perinuclear space (PNS). The inner nuclear membrane contains specific integral proteins that include Sun1 and Sun2. Although the outer nuclear membrane (ONM) is continuous with the endoplasmic reticulum, it is nevertheless enriched in several integral membrane proteins, including nesprin 2 Giant (nesp2G), an 800-kD protein featuring an NH2-terminal actin-binding domain. A recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,440
4
11

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,202 publications
(1,521 citation statements)
references
References 47 publications
45
1,440
4
11
Order By: Relevance
“…Recent biochemical data has demonstrated that SUN-domain proteins are constituents of the inner nuclear membrane and bind KASH-domain proteins (Worman and Gundersen, 2006). SUN-domain proteins are also important for nuclear envelope morphology and link the outer and inner nuclear membranes to the nuclear lamina (Crisp et al, 2006; Figure 2B). …”
Section: Nuclear Envelope Proteinsmentioning
confidence: 99%
“…Recent biochemical data has demonstrated that SUN-domain proteins are constituents of the inner nuclear membrane and bind KASH-domain proteins (Worman and Gundersen, 2006). SUN-domain proteins are also important for nuclear envelope morphology and link the outer and inner nuclear membranes to the nuclear lamina (Crisp et al, 2006; Figure 2B). …”
Section: Nuclear Envelope Proteinsmentioning
confidence: 99%
“…Many of these mutations disrupt assembly of the lamins into the lamina. These mutations also affect nuclear morphology and the localization of other proteins in the nuclear envelope, such as emerin or some of the nesprins-large proteins that connect the nuclear lamina to the cellular cytoskeleton via the LINC complex [36].…”
Section: The A-type Laminopathiesmentioning
confidence: 99%
“…These findings demonstrate that TorA changes the behavior of a subset of LINC complex components, including Sun2 in the INM and nesprin2-Giant and nesprin-3 in the ONM. Indeed, some of the changes in NE membranes caused by redistributed wild-type TorA ( Figure 1BЉ; see also Figure 8A) are reminiscent of changes induced by manipulating components of LINC complexes (Crisp et al, 2006). A recent report of interaction between TorA and nesprin-3 suggests that these effects could be direct (Nery et al, 2008), but further studies are needed to understand the molecular changes involved.…”
Section: Redistributed Tora Displaces a Subset Of Linc Complexmentioning
confidence: 99%
“…SUN proteins participate in NE-spanning LINC complexes (Crisp et al, 2006), which consist of SUN proteins in the inner nuclear membrane (INM) and nesprins in the outer nuclear membrane (ONM; Starr, 2009). Conserved domains of these proteins interact in the perinuclear space to physically connect the nucleus to the cytoskeleton (StewartHutchinson et al, 2008;Starr, 2009).…”
Section: Redistributed Tora Displaces a Subset Of Linc Complexmentioning
confidence: 99%